An Analysis of Text Readability in 9th Grade English Textbook Using FRE Formula on Readable Software - Putri Rafa Salihah; Sahiruddin Sahiruddin; Putu Dian Danayanti Degeng (Unipdu Jombang, 2019)
AbstractThis study measured the readability level of reading texts in English textbook. This study used a text level complexity approach and used quantitative method by utilizing Flesch Reading Ease formula by Rudolph Flesch and calculate by software www.readable.com. The purpose of this study is to find out the readability level of reading texts in English textbook entitled “Bahasa Inggris Think Globally Act Locally SMP/MTs Kelas IX junior high school Published by the Ministry of Education and Culture of Indonesia”. The textbook is revised in 2018 of curriculum 2013. The source of the data in this study were 35 reading texts divided into four levels are: Fairly Difficult, Standard, Fairly Easy, and Easy. While the data in this study were 7 reading texts taken purposively (procedure text, narrative text and report text). The result showed that the textbook is not readable to IX grade of Junior High School. By a final average of71.54 is